Pengembangan Game SIRAJA Berbasis Articulate Storyline 3 untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas V - Aris Dwiyanto; Tri Joko Raharjo; Supriyadi Supriyadi; Nuni Widiarti; Fathur Rokhman; Barokah Isdaryanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Teachers need to strive for innovation in creating new media so that the learning of Natural Sciences becomes easier for students. The purpose of this research is to describe the characteristics, validity, and effectiveness of SIRAJA in enhancing critical thinking skills. This research is a type of developmental research. The researcher used various methods to collect data, including interviews, questionnaires, observations, documentation, and tests. The researcher used a one-group pretest-posttest experimental design. The data obtained was then tested for effectiveness, normality, and the increase in critical thinking scores from the pretest and posttest based on the Hake gain. Meanwhile, the responses from the student and teacher questionnaires were evaluated using a Likert scale. The analysis of the learning outcomes of the respondents, who were the subjects of the study, showed that the pretest score of 59 increased to 77 on the posttest. The percentage of learning mastery also significantly increased, from 20% on the pretest to 85% on the posttest. The normality test used was the one-sample Shapiro-Wilk test, which found an asymptotic significance value of 0.388 for the pretest and 0.616 for the posttest, exceeding the significance level of 0.05. Therefore, the researcher concluded that the utilization of SIRAJA positively impacts the critical thinking of fifth-grade students.